Production porcine dans les fermes d'Etat à Ho-Chi-Minh Ville/Viet-nam - Franceschetto, ML.; Derom, M. (Tropicultura, 1983)
Pig production in State farms at Ho-Chi-Minh Ville. Vietnam. An inquiry carried out in Guinea has revealed that the disappearance of trypanotolerance within some local N'Dama cattle can not be attributed to the vaccination campaign initiated against infectious bovine pleuropneumonia but to diverse environmental and animal management factors prevalant in these areas.